DNA Relatedness, Phenotypic Characteristics, and Antimicrobial Susceptibilities of Globicatella sanguinis Strains - Shewmaker, P. Lynn (American Society for Microbiology, 2001)
DNA-DNA reassociation was performed on 15 strains of Globicatella sanguinis to compare their taxonomic status with phenotypic characterization. All 15 strains selected for DNA-DNA reassociation readily met the criteria for species relatedness. The relative binding ratio was 81% or greater at the optimal temperature and 76% or greater at the stringent temperature, and the divergence was less than 3% for all strains hybridized with the type strain. These strains included nine strains from the Centers for Disease Control Streptococcus Laboratory culture collection that were previously included in comparative 16S rRNA gene sequencing studies as well as six additional phenotypically variant isolates. DNA-DNA relatedness was less than 18% at the optimal reassociation temperature to Aerococcus viridans, Enterococcus avium, and Streptococcus uberis, which are phenotypically similar to G. sanguinis. This study confirms these Globicatella strains were previously misidentified as S. uberis or S. uberis-like strains based on biochemical characteristics. The biochemical data from 28 strains was compiled to further define the phenotypic criteria for identification of this species. A revised description of the species should be variable reaction for pyrrolidonylarylamidase production (75% positive), positive reaction for the bile esculin test (100%), growth at 45°C (96%), variable reaction for acid production from arabinose (45% positive), and negative starch hydrolysis (0% positive). We also evaluated four rapid identification systems, the Biomerieux rapid ID32 STREP (ID32), the Crystal rapid gram-positive identification (Cry4), the BBL Crystal gram-positive identification (Cry24), and the Remel IDS RapID STR (IDS) systems for their ability to identify these strains.